Work Life Balance and Job Satisfaction among the Working Women in Banking Sector: An Empirical Study with Reference to Bangalore City - Naidu, Dr. N. Gurunatha; Chakravarthy, Dr. Parle Kalyan; Touhid, Dr. Patan (The journal of contemporary issues in business and government, 2022)
Work-life balance is one of the supreme challenging issues being encountered by the women employees in the 21st century. Work- life balance means the extent to which the employee feels contented and have his or her needs fulfilled in both professional and personal faces of life. In the recent time the issue of work-life balance has gained more concern due to the reason that an individual’s work life and personal life may present contradictory demands, while demand from both the spheres are equally important. Work life balance and Job satisfaction are the prominent research studies that most of the companies are investing their time to identify various job satisfaction variables. Present study makes an attempt to study the job stress and the work life balance of women employees working in public sector banks in Bangalore City. The study was carried out on primary data from State bank of India, Indian Overseas Bank and Punjab National Bank with sample of 212. . The data are analyzed using various statistical tools and methods on SPSS 28. Present study reveals that there exists a relationship between job stress and work-life balance among working women in selected banks.